DO THE EXTRA ADDITIONAL FACILITIES CREATE A DESIRE AMONG VISITORS TO REVISIT THE SITE? - Wiwin Arisanti; Rishma Anandha Rachmayanti; Tira Pasama (MESP–FEB UNS, 2024)
As an effort to improve the economy through the tourism sector, the management of Prambanan Temple, namely PT Taman Wisata Candi Borobudur, Prambanan, and Ratu Boko, updated regulations by enhancing facilities in the Prambanan Temple area to attract local and international tourists. This research applies contingent valuation methods (CVM) to determine the benefits of the existence of Prambanan Temple and analyze the factors that influence tourist visits to Prambanan Temple facilities. Based on the Willingness To Pay (WTP) value given by tourists, the value of the benefits of existence from Prambanan Temple tourism is IDR 104,658,080,000 or 6,737,949.99. The regression test results show that ticket prices positively and significantly influence tourists' return visits to Prambanan Temple facilities. Meanwhile, the variables education, age, facilities, and services do not have a substantial influence on the level of tourist return visits.